Confined Growth of Silver–Copper Janus Nanostructures with 100 Facets for Highly Selective Tandem Electrocatalytic Carbon Dioxide Reduction. Issue 19 (5th April 2022) - Ma, Yangbo; Yu, Jinli; Sun, Mingzi; Chen, Bo; Zhou, Xichen; Ye, Chenliang; Guan, Zhiqiang; Guo, Weihua; Wang, Gang; Lu, Shiyao; Xia, Dongsheng; Wang, Yunhao; et al.
Abstract: Electrocatalytic carbon dioxide reduction reaction (CO2 RR) holds significant potential to promote carbon neutrality. However, the selectivity toward multicarbon products in CO2 RR is still too low to meet practical applications. Here the authors report the delicate synthesis of three kinds of Ag–Cu Janus nanostructures with 100 facets (JNS‐100) for highly selective tandem electrocatalytic reduction of CO2 to multicarbon products. By controlling the surfactant and reduction kinetics of Cu precursor, the confined growth of Cu with 100 facets on one of the six equal faces of Ag nanocubes is realized. Compared with Cu nanocubes, Ag65 –Cu35 JNS‐100 demonstrates much superior selectivity for both ethylene and multicarbon products in CO2 RR at less negative potentials. Density functional theory calculations reveal that the compensating electronic structure and carbon monoxide spillover in Ag65 –Cu35 JNS‐100 contribute to the enhanced CO2 RR performance. This study provides an effective strategy to design advanced tandem catalysts toward the extensive application of CO2 RR. Abstract : Through breaking the common symmetric growth, three kinds of silver‐copper Janus nanostructures with 100 facets are synthesized with a wet‐chemical method. Coupling the tandem catalysis, copper 100 facets, and electron transfer between silver and copper, the obtained Janus nanostructures demonstrate excellent Faradaic efficiency toward both ethylene and multicarbon products in electrochemical carbon dioxide reduction reaction.